ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ЭТНОГРАФИЗМЛЕРДИҢ АФФИКСАЦИЯ УСЫЛЫ МЕНЕН ЖАСАЛЫЎЫ - Сабурова, А.А. (SCIENCE and SOCIETY, 2017)
The article is devoted to the issues of forming ethnographisms by one of the productive ways of word formation -affixation.